Health Tourism Management: the Case of Thai Health Tourism Industry - Phinaitrup, Boon-Anan (NIDA Development Journal, 2018)
The purpose of the article is to focus on the mechanism that the state utilizes in supporting and developing the health tourism including the relationship with industry and their roles and responsibilities for creating longevity in the health tourism industry in Thailand.The data for this study was collected through purposive sampling method. In-depth interviews were conducted with thirty (30) managers from the Department of Health Services Support in the Ministry of Public Health and the Department of Tourism and the Tourism Authority of Thailand in the Ministry of Tourism and Sports. The results showed that 3 main public mechanisms for thepromotion of health tourism are used for the promotion of the health tourism industry in Thailand. The main mechanisms used in the promotion of health tourism are, the Department of Health Services Support in the Ministry of Public Health, Department of Tourism, and the Tourism Authority of Thailand in the Ministry of Tourism and Sports. However, each of these three-mechanism had unique approaches to managing and promoting health tourism in the country. For example, the Department of Health Service Support monitors the quality control system for health services products and health services businesses, the Department of Tourism establishes the basic foundations of tourism, facilitates tourism in the country. And the Tourism Authority of Thailand markets the brand and identity of the country both domestically and internationally. Moreover, the mechanisms that are important in turning policy into action and increasing competitiveness revealed that strong organizations with a specific mission and clear working guidelines had a direct influence on health promotion.